On the iconography of the gold foil figures from Hauge (AmS-Skrifter, 2026)
The 16 gold foil figures from Hauge depict a man and a woman embracing each other. This scene is very common on Scandinavian gold foils of the Merovingian Period and often is interpreted as a pair of gods or as a wedding rite. What particularly distinguishes the find from Hauge is a staff or plant stem that the woman seems to be holding in her hand. In this paper, I will explore the meaning of this plant, which can also be seen on other Iron- and Viking-age pictorial representations and, against the background of a very rich literary and runic tradition, can be understood as an allium plant, a leek. Since antiquity as well as in the north, this plant has been attributed magical powers and healing properties and was associated with fertility and sexuality.